Apoptose relacionada à infecção in vitro por herpesvírus bovinos tipo 1 e 5 - Novais, Juliana Bueno de [UNESP] (2014)
Bovine Herpesvirus type 5 (BoHV-5) and bovine herpesvirus type 1 (BoHV-1), members of Herpesviridae family, Alphaherpesvirinae subfamily; may replicate in different tissues such as nervous, glandular, lymphoid and parenchymal organs and are able to remain in a latent state, lodged in nerve ganglia. In Brazil clinical cases of BoHV - 5 encephalitis are the second leading cause of death due to encephalitis with determined etiology, supplanted only by rabies, while the BoHV-1 is present in an endemic form in the national herd, being responsible for a variety of clinical signs as rhinotracheitis, abortion, conjunctivitis, vulvovaginitis and balanoposthitis. It is expected that a viral agent, to infect a cell, activate the pathways of programmed cell death process, however there are reports that the gene related to latency (RL) of Herpesvirus is able to inhibit cell apoptosis, protecting the infected cell during latency through unknown mechanisms. Therefore, this study demonstrated the capacity of BoHV-5 and BoHV-1 to manipulate mitochondrial metabolism of the infected cell, interfering with intrinsic pathway of apoptosis